A filosofia dionisíaca de Nietzsche: supressão da metafísica e pathos afirmativo - Catafesta, Leonardo Augusto (2010)
This paper aims to investigate the conception of Dionysian philosophy presented by Friedrich Nietzsche in his final writings. The German philosopher articulates the Dionysian notion along with the notion of Apollo in his first published book, namely, The birth of the tragedy (1872). In this work, there is a direct influence of Wagner s music and Schopenhauer s philosophy in the main theoretical conceptions, thus initiating a metaphysic of artist because, according to his conception, life can only be vindicated while aesthetic phenomenon. Since his work Too human (1878), the Dionysian concept disappears from Nietzschian texts, even in later fragments, returning only in the so called third phase, that is, from Thus spoke Zarathustra (1883), this time under a new approach Nietzsche completely disengages himself from Wagner and Schopenhoauer by not working with the metaphysic of artist or using the concept of Apollo. With a more mature thinking, the German philosopher diffuses his Dionysian philosophy proposing to be completely free from the metaphysic and at the same time affirming existence without boundaries. To do so, it is mainly necessary to transpose the Dionysian into philosophical pathos. Nietzsche makes use of tragic wisdom as the main instrument for such transposition for, only then, one can converse as regards Dionysian philosophy. Understanding tragic wisdom not as theoretical knowledge, but as the understanding and acceptance of the incessant fight that pervades all fractions of life, Nietzsche can declare himself as the first tragic philosopher. Not to fall in pessimism that depreciates life, due to his relentless fighting character, the philosopher exploits game notion. With it, man establishes common sense to the coming-to-be, interlining himself as supreme creator. Thus, a child s image is the example of the most skillful player because he or she inexorably throws him or herself at it without worrying about victory or defeat -- the important thing is to play the game. Hence, the path to understand Dionysian philosophy without presupposed metaphysisists is open. For Nietzsche metaphysic is articulated with the duplication of worlds a real world is envisioned as a condition of the apparent world . Having the need for truth as modus operandi, metaphysic mendaciously created a fixed and immutable world to justify the flow from the coming-to-be. According to the nietzschinian view, this entails the denial of effectiveness because by privileging the real world the apparent world is refuted, the only sphere on which the phenomenon life is possible. With the conception of the eternal recurrence of it, Nietzsche reaches a thought without metaphysic duality, overcoming the instant/everlasting dichotomy. For the metaphysic tradition, eternity has always been transcendent to the instant, as the eternal recurrence, eternity and instant have become equivalent, in other words, the instant is conceived as eternal. Moreover, to reach supreme affirmation of eternal recurrence, Nietzsche has notion of amor fati as being the great formula for the Yes, ie, of unrestricted affirmation for joy and pleasure as well as pain and suffering. In this sense, we can understand the Dionysian philosophy proposed by Nietzsche in his last writings while total suppression of affirmative pathos and metaphysic par excellence.